Difference Equations, Discrete Dynamical Systems and Applications ICDEA, Wuhan, China, July 21-25, 2014 - Bohner, Martin; Ding, Yiming; Došlý, Ondřej; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
These proceedings of the 20th International Conference on Difference Equations and Applications cover the areas of difference equations, discrete dynamical systems, fractal geometry, difference equations and biomedical models, and discrete models in the natural sciences, social sciences and engineering. The conference was held at the Wuhan Institute of Physics and Mathematics, Chinese Academy of Sciences (Hubei, China), under the auspices of the International Society of Difference Equations (ISDE) in July 2014. Its purpose was to bring together renowned researchers working actively in the respective fields, to discuss the latest developments, and to promote international cooperation on the theory and applications of difference equations. This book will appeal to researchers and scientists working in the fields of difference equations, discrete dynamical systems and their applications.
The Beverton–Holt q-Difference Equation with Periodic Growth Rate -- Spectral Measures on Local Fields -- Pullback and Forward Attractors of Nonautonomous Difference Equations -- Necessary and Sufﬁcient Conditions for Hyperbolicity -- On Hausdorff Dimension of Invariant Sets for a Class of Piecewise Linear Maps -- Generalized Zeros and Nonpositivity of Energy Functionals associated with Half-Linear Even-Order Difference Equations -- Eigenvalue Comparison for Discrete Symplectic Systems -- Cookie-Cutter-like Dynamic System of Unbounded Expansion -- A Discrete Dynamic Model for Computer Worm Propagation -- Almost Periodic Solutions of Neutral Functional Dynamic Systems in the Sense of Stepanov -- On A Linear Delay Partial Difference Equation with Impulses -- Nonstationarity of Stock Returns -- Pricing Convertible Bonds with Credit Risks and Stochastic Interest Rates -- Dynamical Systems Disjoint from any Minimal System under Group Actions.
Keywords: Difference equations; Functional equations; Dynamics; Ergodic theory; Applied mathematics; Engineering mathematics; Biomathematics; Mathematical models; Difference and Functional Equations; Dynamical Systems and Ergodic Theory; Applications of Mathematics; Genetics and Population Dynamics; Mathematical Modeling and Industrial Mathematics